Rare Occasions: Tidal Disruption Events Rarely Power the AGNs Observed in Dwarf Galaxies - Joanne Tan; Guang Yang; Jonelle L. Walsh; W. N. Brandt; Bin Luo; Franz E. Bauer; Chien-Ting Chen; Mouyuan Sun; Yongquan Xue (The Astrophysical Journal)
Tidal disruption events (TDEs) could be an important growth channel for massive black holes in dwarf galaxies. Theoretical work suggests that the observed active galactic nuclei (AGNs) in dwarf galaxies are predominantly TDE-powered. To assess this claim, we perform variability analyses on the dwarf-hosted AGNs detected in the 7 Ms Chandra Deep Field-South survey, with observations spanning ≈16 yr. Based on the spectral energy distribution modeling with x-cigale , we select AGNs hosted by dwarf galaxies (stellar mass below 10 ^10 M _⊙ ). We focus on X-ray sources with full-band detections, leading to a sample of 78 AGNs (0.122 ≤ z ≤ 3.515). We fit the X-ray light curves with a canonical TDE model of t ^−5/3 and a constant model. If the former outperforms the latter in fitting quality for a source, we consider the source as a potential TDE. We identify five potential TDEs, constituting a small fraction of our sample. Using true- and false-positive rates obtained from fitting models to simulated light curves, we perform Bayesian analysis to obtain the posterior of the TDE fraction for our sample. The posterior peaks close to zero (2.56%), and we obtain a 2 σ upper limit of 9.80%. Therefore, our result indicates that the observed AGNs in dwarf galaxies are not predominantly powered by TDEs.